Fertility, conception and complications in elderly primigravidas a comparative study: observational study - Sabha, Madieha; Bashir, Khushbu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Incidence of elderly primigravida has increased now days, due to rising education level, effective means of birth control and high carrier goals. The women who conceived at advanced age (>35 years) for first time is defined as elderly primigravida. Indian standard is fixed at more than 30 years by Dutta 2013. These women are high risk for maternal and foetal complication and outcome. The study was done to assess pregnancy outcome in elderly primigravida. Methods: This was a prospective comparative study done in 180 patients over a period of 18 months from September 2017 to March 2019. Among 180 patients 90 patients were elderly primigravidas more than 30 years of age and 90 patients were young primigravidas aged 20 to 29 years. Results: Majority of elderly women though married early, conceived late, many women required other ovulation induction to ART dueto many associated complication with elderly primigravida C-section rate is higher in elderly as compared to vaginal delivery. Conclusions: Elderly primigravida >30 years old had more difficulty in conceiving spontaneously as the fecundity is less with advanced age. The need for ovulation induction and other artificial reproductive techniques is higher in women with advanced age. The complications during pregnancy, labour and postpartum is higher in elderly primigravidas as compared to women less than 30 years of age.